The Effectiveness of Emotional Focused Couple Therapy on Marital Burnout and Attitudes toward Infidelity of Couples - Shifteh Shahabi; Gholamreza Sanagouye-Moharer (Shahid Beheshti University of Medical Sciences, 2019)
Background and Objective: Emotional focused couple therapy (EFCT), which is a structured and short-term approach, has a widespread application in solving emotional problems of couples. The purpose of this study was to determine the effectiveness of emotional focused couple therapy on marital burnout and attitudes toward infidelity of couples. Materials and Methods: This study was of semi-experimental design with pre-test and post-test and control group. The statistical population included all couples in counseling centers in Kerman who were selected by convenience sampling method and 60 individuals, 30 couples, were randomly divided into two experimental and control groups, each including 30 individuals. The research instruments were questionnaire of Attitude towards Infidelity scale and Marital Burnout Inventory. To analyze the data, analysis of covariance analysis was performed using SPSS software version 22. Results: The mean (SD) age of the experimental group was 39.5 (1.6) and the control group 37.8 (6.5). The mean (SD) score of marital burnout in the pre-test of the experimental group was 6.7 (0.5) which decreased to 3.2 (0.3) in the post-test (P <0.001). The mean (SD) score of attitudes toward infidelity in the experimental group was 42.3 (7.8) in the pretest which decreased to 36.4 (6.3) in post-test (P <0.001). The witnessed decrease in the scores of participants was higher in the experimental group than in the control group. Conclusion: The study showed that the emotional focused couple therapy can reduce marital burnout and permissive attitudes toward infidelity. DOI: http://doi.org/10.22037/ch.v7i1.23086